ADAPTASI TEKNOLOGI DAN PERMASALAHAN KAPASITAS SUMBER DAYA MANUSIA DI WISATA KAMPUNG ADAT SEGUNUNG - Prasandi, Djenggala; Nuryananda, Praja Firdaus (Tulisan Ilmiah Pariwisata (TULIP), 2024)
This article is the result of a study, desk and field research, which was carried out by a team of researchers at the tourist destination of the Kampung Adat Segunung, Carangwulung Village, Jombang, Indonesia. Kampung Adat Segunung has adapted digital technology to encourage their tourism, such as creating a website page, creating Instagram social media, and utilizing the loket.com application as an online ticketing system. However, the adaptations that were made did not automatically encourage tourism in Segunung to become more advanced. Kampung Adat Segunung is now burdened with their dependence on third parties as parties who provide ICT instrument management services for Kampung Adat Segunung. By using a descriptive-qualitative method, the research conducted found that the premise of digital technology adaptation can help the advancement of tourist destinations seems to have to be revised slightly. Adaptation of digital technology must meet the contextual requirements of the location where tourism is located so that it can run more effectively and succeed in driving progress. Kampung Adat Segunung has difficulty identifying this, even though the existing human resources are still not qualified to adapt digital technology. Data collection was carried out by means of library research, participatory observation, and in-depth interviews with the tourism managers of the Kampung Adat Segunung.